Cone Beam Computed Tomography – Applications in Orthodontics - Singh, Shikha; Singh, Gautam; Prakash, Amit (Orthodontic Journal of Nepal, 2016)
.Orthodontic Journal of Nepal, Vol. 6 No. 1, June 2016, pp.35-36